Endocrine immunology - Savino, Wilson; Guaraldi, Federica (Frontiers of hormone research / series editor Ezio Ghigo, 2017)
In the last decades, several in vitro and in vivo studies have revealed the existence of a very complex network between the neuroendocrine and immune system. Important molecular mechanisms underlying these interactions, in both physiological and pathological conditions, have also been described. Indeed, hormones play a pivotal role in the development and functional regulation of the immune system - both innate and acquired responses. Immune system cells present specific hormone receptors and themselves produce some hormones, thus influencing hormone secretion. More recently, the modulation of hormone secretion has been attempted for treating associated autoimmune disorders, further supporting the strong interplay between the endocrine and immune system. Distinguished experts, who have published extensively in their fields, have contributed comprehensive chapters to this volume. The focus is on the various aspects of endocrine-neuro-immune connections, providing an updated panorama - from basics to clinical applications - of current knowledge and still debated issues.